The Assessment of the Factors Affecting the Enrollment Procedure in Registrar Department at Bestlink College of the Philippines, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study assessed the factors that may affect the enrollment procedure at BestlinkCollege of the Philippines in Quezon City. Due to unexpected circumstances, the college hadto adopt remote or online enrollment, necessitating adjustments to enrollment procedures. Asa result, there were several factors that needed to be considered in order to achieve efficiency.The study found that the respondents strongly agreed that several factors affected theenrollment procedure. The researchers hypothesized that the demographic profile ofrespondents directly affected the enrollment procedure at Bestlink College of the Philippines.The findings of the study showed that the registrar department was being affected by theinternet connection, digital literacy, and delegation management in various ways, especially inthe enrollment procedure.The researchers concluded that there was a need for a better and smoother enrollmentprocedure to be put in place, as both the researchers and the record officers desired. Thisresearch revealed that the enrollment procedure needs to be improved or enhanced in orderto overcome the future issues that it may face. Remote enrollment and walk-in enrollmentshould be stable to prevent confusion among those who used it. For remote enrollment, it onlytakes one website for a student to enroll, check balance, grant modules, etc. To avoidconfusion and account loss due to a lot of passwords and accounts to remember. In addition,the budget for a second network provider should be taken into account by the collegeadministration in order to cover the registrar department's network loss during the enrollmentseason. Overall, the study demonstrated the importance of assessing factors that may affectenrollment procedures in an educational institution, particularly during unexpected changes.
Keywords: Business